Hubungan Antara Motivasi Belajar Dengan Kemampuan Siswa Dalam Melakukan Senam Lantai Guling Depan pada Siswa SMPN 1 Karawang Timur - Fadhillah, Muhammad Ridwan; Sumarsono, Rhama Nurwansyah; Yuda, Aria Kusuma (Indonesian Journal of Education and Development Research, 2025)
This study aims to determine the relationship between learning motivation and students' ability in performing forward roll floor gymnastics at SMPN 1 Karawang Timur. The background of this research is based on field findings that most students experience difficulties in performing the forward roll movement, which is suspected to be caused by a lack of learning motivation, fear of injury, and low self-confidence. This study employs a quantitative approach with a correlational method. The instruments used include a learning motivation questionnaire and a practical test of forward roll skills, with a sample of 36 students selected purposively. Based on the data analysis, a correlation coefficient of 0.845 was obtained, which falls into the strong category, along with a significance value of 0.000 (p 0.05), indicating a positive and significant relationship between learning motivation and the ability to perform the forward roll. These results suggest that the higher the students' learning motivation, the better their ability to master the gymnastics movement. This research highlights the importance of motivation in the physical education learning process and recommends that PE teachers develop teaching strategies that can enhance students' motivation in motor learning.